Legal Protection for Creditors in Commercial Property Disputes (Case Study of Batam District Court Decision No. 158/Pdt.G/Plw/Gs/2022/Pn Btm) - Malau, Hotmaulina; Nurlaily, Nurlaily; Disemadi, Hari Sutra (Journal of Law, Politic and Humanities, 2025)
Commercial property disputes are one of the significant challenges in business practice in Indonesia, especially in the legal relationship between creditors and debtors. This study aims to analyze legal protection for creditors in commercial property disputes through a case study of the Batam District Court Decision No. 158/Pdt.G/Plw/GS/2022/PN Btm. The methodology used is normative legal research with an analytical-descriptive approach, which examines laws and regulations and related court decisions. The results of the study show that in this case it includes three dimensions of legal protection according to Philipus M. Hadjon's theory, namely preventive, repressive, and curative. In the preventive dimension, protection is provided through the binding of dependent rights and the use of the cession mechanism as an anticipatory measure. The repressive dimension, lawsuits and cession recognition by the courts ensure that creditors' rights remain protected after a dispute has occurred. The curative dimension, guarantee execution and litigation process play a role in the recovery of creditor rights due to debtor default. However, the study also found weaknesses in the implementation of legal protection, especially related to the long legal process and bureaucracy in the execution of bail. This study concludes that legal protection for creditors in Indonesia has been well regulated normatively, but its implementation needs to be strengthened, especially in the efficiency of guarantee execution and dispute management. Recommendations are given to creditors, debtors, and governments to improve dispute management and legal protection within the commercial property sector